A LITERATURE REVIEW OF SOCIAL ENTREPRENEURSHIP: A SOLUTION FOR CHALLENGES IN THE GIG ECONOMY - Shalsabilla Shafira; Ritha F. Dalimunthe (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The gig economy, a rapidly growing economic phenomenon, has transformed traditional employment paradigms and modern economic structures. It reflects a flexible labor market based on demand, occasional work, and typically task-based arrangements. However, the presence of the gig economy also poses various challenges for its workers, such as income uncertainty, lack of social protection, job instability, and uncertain working hours. To address these challenges, social entrepreneurship emerges as a potential solution. With a creative and sustainable approach, social entrepreneurship can enhance the well-being and fairness for gig workers, as well as create a more equitable and inclusive work environment. This research explores the role of social entrepreneurship in addressing issues in the gig economy, with the hope of serving as a valuable source of information for gig workers, particularly in Indonesia.